Hospitalization following pediatric kidney transplantation: An international comparison among a Canadian pediatric transplant center, North American Pediatric Renal Trials and Collaborative Studies, and Cooperative European Pediatric Renal Transplant Initiative registry data. (27th March 2022) - Kim, Jin K.; Lorenzo, Armando J.; Tönshoff, Burkhard; Chua, Michael E.; Raveendran, Lucshman; Krupka, Kai; Teoh, Chia Wei; Ming, Jessica M.; Topaloglu, Rezan; Dello Strologo, Luca; Farhat, Walid A.; Koyle, Martin A.
Abstract: Background: There are several databases across the world that collect pediatric KT data. We compare the hospitalization outcomes for pediatric KT recipients from a large Canadian transplant center (SickKids database; The Hospital for Sick Children Kidney Transplantation Institutional Database), United States (NAPRTCS), and Europe (CERTAIN registry). Methods: An institutional retrospective review of KT was performed between 2000 and 2015. Baseline characteristics, duration of initial hospitalization/readmission at 1–5 and 6‐ to 11‐month posttransplant, and 1‐year graft survival data were collected. Corresponding data from the NAPRTCS 2014 Annual Transplant Report and CERTAIN registry were compared. Results: Posttransplant, patients from NAPRTCS had the shortest duration of hospitalization within the first month (10.4 days, SE 0.2), followed by SickKids (20.3 days, SE 0.7) and CERTAIN (25.5 days, SE 0.7). For both living and deceased donor populations, patients from SickKids were most likely to be hospitalized at 1‐ to 5‐month posttransplant (82.4% [89/108]; 72.1% [98/136]), followed by Europe (52.1% [198/380]; 61.6% [501/813]) and United States (45.4% [2379/5241]; 51.4% [2517/4896]). Patients from Europe were most likely to be hospitalized at 6‐ to 12‐month posttransplant (42.1% [160/380]; 51.7% [420/813]), followed by SickKids (35.2% [38/108]; 37.5% [51/136]) and United States (28.3% [1387/4901]; 31.6% [1411/4465]). Across all databases, the most commonly addressed issues during readmissions were infectious complications. Conclusion: The differences observed in this investigation may reflect the local reimbursement models, resources for outpatient management, and practice variations across a large Canadian transplant center, United States, and European countries.